Spanish judo success at the international level: a historical perspective - Gutiérrez García, Carlos; Santos, Luis; Montero-Carretero, Carlos; Escobar-Molina, Raquel (Revista de Artes Marciales Asiáticas, 2018)
The aim of the present study was to collect and analyze the sporting successes of Spanish judo (senior category) in the Olympic Games, World Championships and European Championships. Data collection was made through several websites specific to judo. Until May 2018, Spanish judo achieved a total of 141 medals (six in the Olympic Games, 21 in the World Championships and 114 in the European Championships). Most medals were achieved in the 1990s and 2000s, as in the decade of 2010 a significant reduction is taking place. Successes were greatest for women, adding up to 69.5% of the total medals and, qualitatively, the most relevant successes for Spanish judo.